THE ABILITY OF ISLAMIC RELIGIOUS EDUCATION TEACHERS AT JUNIOR HIGHT SCHOOL TAPAKTUAN IN USING THE MERDEKA MENGAJAR PLATFORM - Pramulya Utama; Zulfatmi Zulfatmi; Saifullah Maysa (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh, 2025)
The purpose of this study was to see the ability of Islamic Religious Education teachers at Tapaktuan Junior High School in using the Merdeka Mengajar Platform. This study uses a quantitative method. This study was located at Tapaktuan Junior High School. The sample in this study were Islamic Religious Education teachers who had a Merdeka Mengajar Platform account. There were 5 Islamic Religious Education teachers who had a Merdeka Mengajar Platform account. The data collection techniques used in this study were questionnaires and observations. The data analysis technique used a percentage formula, then analyzed using descriptive statistics. The results of this study are that most Islamic Religious Education teachers in Tapaktuan are not yet fully able to use the Merdeka Mengajar Platform. These teachers still need to improve their abilities in all the features available on the Merdeka Mengajar Platform. While a small number of Islamic Religious Education teachers are already able to use the Merdeka Mengajar Platform, they still need to improve their abilities in the Student Assessment and Work Results features. Keywords: Merdeka Mengajar Platform, Independent Curriculum